Optimizing Care Teams by Leveraging Advanced Practice Providers Through Strategic Workforce Planning. (September 2022) - Kuriakose, Clair; Stringer, Meredith; Ziegler, Amy; Hsieh, Chuyun; Atashroo, Megan; Hendershott, Joan; Tippett, Vicki; Shah, Deepa; Cianfichi, Lisa; Katznelson, Laurence; Mahoney, Megan
Abstract : INTRODUCTION: Advanced practice providers (APPs) are integral members of the healthcare delivery team. However, there has been a lack of standardization and uniformity in how they are utilized across inpatient, ambulatory, and procedural settings. METHODS: A multidisciplinary workforce planning committee was formed in March 2021 to evaluate all new and replacement full-time equivalent APP positions at Stanford Health Care (SHC), an academic medical center of more than 600 APPs, to optimize and standardize the role of APPs as per national benchmarks. RESULTS: Six months since the launch of the committee, there has been a 10% increase in the number of visits and procedures performed by APPs providing better access for patients. In addition, there has been a 38.7% improvement in ambulatory APPs meeting their productivity target, 19.4% improvement in ambulatory APPs meeting utilization targets, and 36.8% improvement in ambulatory APPs meeting the 50th percentile and above as per the relative value unit benchmark published by the Medical Group Management Association for Academic Medical Centers. For inpatient APPs, there has been a 38.8% improvement in APPs meeting the average daily census target. DISCUSSION: APP utilization is an important topic that has not been consistently addressed in the literature. Inappropriate utilization and lack of top of licensure practice have been associated with increased turnover, decreased job satisfaction, and professional development. By developing a multidisciplinary workforce planning committee, full-time employee positions are evaluated with a goal of optimizing and standardizing the role of APPs at SHC.